KOMPONEN SERAT JERAMI JAGUNG DAN JERAMI SORGUM SETELAH DI FERMENTASI DENGAN Phanerochaete chrysosporium - Abdullah, Sirajuddin (JSTT, 2011)
Abstract: The fermentation of corn straw fiber and sorghum straw by using Phanerochaete chrysosporium fungus is done to improve its nutrition quality. This research was done in a laboratory by using a Complete Random Plan with factorial pattern of 2 x 4 and was repeated 3 times. The first factor was the type of straw, they were corn and sorghum straws. The second factor was the dosage of fungus inoculumss of Phanerochaete chrysosporium, each in 0% v/w (Pc0), 2% v/w (Pc1), 4% v/w (Pc2) and 6% v/w (Pc3). When there was a real difference, it was then continued Different Real Honest Test. The use of fungus inoculums of Phanerochaete chrysosporium in real has improved the content of ADF (2,92%), cellulose (3,59%), and has really decreased the content of NDF (1,85%), hemicellulose (7,48%), and the content of lignin (7,26%).Â  There was no interaction between the type of straw with the dosage of fungus inoculums of Phanerochaete chrysosporium towards the changes in the content of NDF, ADF, hemicellulose, cellulose, and lignin.Â  Corn straw has real high content of ADF, cellulose, and really decrease the content of NDF, lignin, and hemicellulose. Based on the effect of fermentation of Phanerochaete chrysosporium fungus, 6% v/w (Pc3) dosage was better as the inoculums of corn straw and sorghum straw, which was able to improve the quality of straw as food so that it has enough nutrition as an alternative food. Key words: Straw, Phanerocaete chrysosporium, Fiber.